Kebijakan Pemerintah Filipina dalam Menangani Ancaman Gerakan Moro Islamic Liberation Front - MS, Aunur Rafiq; Putranti, Ika Riswanti; Pertiwi, Sheiffi Puspa (Journal of International Relations, 2017)
The issue of terrorism and separatism are common in recent years. Both problems can arisebecause of radical thinking that develops within a group. Moro Islamic Liberation Front(MILF) is one example of groups related to terrorism and separatism. The group wants toform its own state or independent from the Philippines, which then leads to conflictbetween the Philippines and MILF. The existence of cooperation that is established withseveral terrorist groups expose threats in the form of physical or thought. The PhilippineGovernment has issued several policies that are expected to resolve the conflict with theMILF. This study aims to understand how the policies undertaken by the Philippines inresolving conflicts with the MILF. This research uses constructivism paradigm andproblem solving theory with qualitative method. From the research that has been done, it isknown that the Philippines uses the method of hard approach and soft approach in order tosolve the problem. However, the soft approach method is more often used in terms ofnegotiation and mediation. This proves the Philippines has applied the value of democracyto deal with the problem.